An Analysis of Cognitive Levels on Questions Used for Examination in SMP Negeri 15 Padang - Putri Styvani; Hamzah Hamzah (Journal of English Language Teaching, 2022)
This study was descriptive research which aimed to find out distribution of questions for examination within cognitive domains in SMP Negeri 15 Padang. The data were derived from examination questions. The questions from examination were analyzed and classified based on cognitive levels of Revised Bloom’s Taxonomy by Anderson and Krathwohl (2001). The examination questions were collected from grade VII, VIII, and IX. The results of the study show that there are significant imbalances in the distribution of questions within cognitive levels for examination. From all grades, LOTS-based questions dominantly found in examination question. Specifically, Understanding (C2) and Applying (C3) level of questions dominated the distribution of questions in SMP Negeri 15 Padang.  Meanwhile, only Analyzing (C4) level of question found in HOTS category. However, the percentages of HOTS-based questions are higher than LOTS-based questions found in examination.